A Speech Act Analysis of Nadiem Anwar Makarim’s Speech - Lia Rosdiana (Universitas Pendidikan Ganesha, 2023)
Speech is the ability to speak in front of the public to tell their opinion or give an idea about something important. This research aimed to analyze the kinds of communication function in illocutionary act in a speech made by Nadiem Anwar Makarim as Ministry of Education as well as identifying the effects contained in the speech made by Nadiem Anwar Makarim. The research used qualitative approach. The approach used in this study is a qualitative approach. In this research to check the correctness of the data from different perspectives, researchers used triangulation. Data analyses used by researchers are consisted of 3 ways in data analysis, namely data reduction, data display and conclusion drawing. The result showed that: 1) All kinds of illocutionary act from Searle were occurred in whichrepresentatives act was the act which was mostly usedin a speech made by Nadiem Anwar Makarim which was 43.66%. Then, in a speech made by Nadiem Anwar Makarim, there was an indication of declaration (14.08%), directives (19.71%), expressives (15.49%) and commissive (4.23%). 2) The speech from Nadiem Makarim was mostly in the form of direct and active sentence (70%). The reason is because Nadiem Makarim state his speech directly by himself, there is no other people or company whom he referred and he mostly used prefix “me” and suffix “kan” to state his speech directly. There is also the form of passive voice, imperative sentence and indirect sentence.